Cerebral Amyloid Angiopathy Is Associated With Executive Dysfunction and Mild Cognitive Impairment. Issue 8 (August 2016) - Case, Nevicia F.; Charlton, Anna; Zwiers, Angela; Batool, Saima; McCreary, Cheryl R.; Hogan, David B.; Ismail, Zahinoor; Zerna, Charlotte; Coutts, Shelagh B.; Frayne, Richard; Goodyear, Brad; Haffenden, Angela; et al.
Abstract : Background and Purpose—: Autopsy studies suggest that cerebral amyloid angiopathy (CAA) is associated with cognitive impairment and risk for dementia. We analyzed neuropsychological test data from a prospective cohort study of patients with CAA to identify the prevalence of cognitive impairment and its associations with brain magnetic resonance imaging features and the apolipoprotein E genotype. Methods—: Data were analyzed from 34 CAA, 16 Alzheimer's disease, 69 mild cognitive impairment, and 27 ischemic stroke participants. Neuropsychological test results were expressed as z scores in relation to normative data provided by the test manuals and then grouped into domains of memory, executive function, and processing speed. Results—: Mean test scores in CAA participants were significantly lower than norms for memory (−0.44±1.03; P =0.02), executive function (−1.14±1.07; P <0.001), and processing speed (−1.06±1.12; P <0.001). Twenty-seven CAA participants (79%) had mild cognitive impairment based on low cognitive performance accompanied by cognitive concerns. CAA participants had similarly low executive function scores as Alzheimer's disease, but relatively preserved memory. CAA participants' scores were lower than those of ischemic stroke controls for executive function and processing speed. Lower processing speed scores in CAA were associated with higher magnetic resonance imaging white matter hyperintensity volume. There were no associations with the apolipoprotein E ε4 allele. Conclusions—: Mild cognitive impairment is very prevalent in CAA. The overall cognitive profile of CAA is more similar to that seen in vascular cognitive impairment rather than Alzheimer's disease. White matter ischemic lesions may underlie some of the impaired processing speed in CAA. Abstract : Supplemental Digital Content is available in the text.